Efficacy of Yun-Type Optimized Pelvic Floor Training Therapy for Middle-Aged Women With Severe Overactive Bladder: A Randomized Clinical Trial - Shi, Chaoliang; Zhou, Dan; Yu, Wandong; Jiao, Wei; Shi, Guowei; Wang, Yangyun (Frontiers in Surgery, 2021)
Background: This study aimed to evaluate the clinical efficacy of Yun-type optimized pelvic floor training therapy for middle-aged women with severe overactive bladder (OAB). Methods: This randomized, observer-blinded, parallel-group controlled clinical trial included 108 middle-age women with severe OAB and assigned them to the intervention group (treated with combination of Yun-type optimized pelvic floor training with solifenacin for 12 weeks) and control group (treated with solifenacin for 6 weeks and, after 2 weeks of elution, received the combination of Yun-type optimized pelvic floor training and solifenacin for 6 weeks). The outcomes associated with OAB, pelvic floor muscle (PFM) function, and sexual function were compared after 6 and 12/14 weeks of treatment. Results: The primary variables were OAB-associated outcomes, including overactive bladder symptom score (OABSS), urgent urination, urine, nocturia, urge urinary incontinence, patient's perception of bladder condition, urogenital distress inventory-6, incontinence impact questionnaire-7, voiding volume, average flow rate, and maximum flow rate. The secondary variables were indicators related to PFM function and sexual function. These indicators were significantly improved in both groups after interventions. Notably, the improvements in most of these indicators were superior in the intervention group than in the control group after 6 weeks and 12/14 weeks of treatment. Conclusions: The use of Yun-type optimized pelvic floor training adds to the benefits of solifenacin regarding severe OAB-associated outcomes, PMF function, and sexual function in middle-aged women with severe OAB. Combining Yun-type optimized pelvic floor training with traditional drug therapies may improve clinical outcomes in patients with severe OAB. Trial registration: ChiCTR-INR-17012189